Cerebrospinal fluid-contacting neurons: a promising source for adult neural stem cell transplantation in spinal cord injury treatment - Luo, Zhangrong; Shangguan, Zeyu; Cao, Liang; Zhang, Yi; Li, Qizhe; Shi, Xuexing; Fu, Jiangquan; Wang, Chunqing; Dou, Xiaowei; Tan, Wei; Li, Qing (Frontiers in Cell and Developmental Biology, 2025)
Transplantation of adult neural stem cells (NSCs) is regarded as one of the most promising approaches for treating spinal cord injury (SCI). However, securing a sufficient and reliable source of adult NSCs remains one of the primary challenges in applying this method for SCI treatment. Cerebrospinal fluid-contacting neurons (CSF-cNs) act as adult NSCs and can be substantially expanded in vitro while maintaining their NSC characteristics even after 60 passages. When CSF-cNs are transplanted into the injury sites of SCI mice, they demonstrate high survival rates along with the ability to proliferate and differentiate into neurons, astrocytes, and oligodendrocytes. Additionally, significant improvements in motor function have been observed in SCI mice following the transplantation of CSF-cNs. These results suggest that CSF-cNs may represent a promising source of adult NSCs for transplantation therapy in SCI.